Endometriosis and Ovarian Cancer: Insights from NHANES and Mendelian Randomization Analysis - Liu, Dong; Wu, Yuke; Zhou, Kunyan (Reproductive sciences (Thousand Oaks, Calif.), 2025)
Endometriosis describes the growth of extra-uterine endometrium, causing pain and inflammation, and the condition has been estimated to affect 10% of women of reproductive age. It remains under-diagnosed and has been linked to increased cancer risk. This study evaluated the correlation between endometriosis and cancer. The significance of specific loci to cancer was analyzed via Mendelian randomization (MR). Of the 4092 samples included, cancer diagnoses were self-reported by 326 women with endometriosis and 3766 women without endometriosis. Correlations between individual cancer types and endometriosis were analyzed by multivariable logistic regression models and odds ratios (OR) adjusted for confounders. Mortality was evaluated by Kaplan–Meier survival analysis. Genetic variants associated with endometriosis were linked to ovarian cancer by MR analysis. Women with endometriosis had a higher association of overall cancer (OR = 1.80, 95% CI: 1.19—2.72) and this was especially the case for ovarian cancer (OR = 11.40, 95% CI: 3.00—43.34). Subgroup and sensitivity analyses confirmed the robustness of these results. Kaplan–Meier analysis indicated lower survival from all causes in women with endometriosis (p = 0.022) but no significant difference in cancer survival. MR analysis supported a positive relationship between endometriosis and ovarian cancer (OR = 1.203, 95% CI: 1.011—1.433). The history of endometriosis was positively associated with the history of overall and ovarian cancer. Women with a history of endometriosis should have access to enhanced cancer surveillance and proactive management. Further research is needed to confirm these associations and to give mechanistic insights. Graphical Abstract